Ice cover alters the behavior and stress level of brown trout Salmo trutta. (31st March 2015) - Watz, Johan; Bergman, Eva; Calles, Olle; Enefalk, Åsa; Gustafsson, Stina; Hagelin, Anna; Nilsson, P. Anders; Norrgård, Johnny R.; Nyqvist, Daniel; Österling, E. Martin; Piccolo, John J.; Schneider, Lea D.; et al.
Lay Summary: Surface ice shelters fish from terrestrial predators. We show that the presence of ice cover reduced stress and increased swimming activity and aggression of trout in artificial streams. Moreover, the effect of ice cover on swimming activity was greatest for trout with high RMRs. Our results may explain why salmonid production is high in ice-covered rivers and should be viewed in light of ongoing global warming that reduces the duration of ice cover. Abstract : Surface ice in rivers and lakes buffers the thermal environment and provides overhead cover, protecting aquatic animals from terrestrial predators. We tested if surface ice influenced the behavior (swimming activity, aggressive encounters, and number of food items eaten) and stress level (coloration of eyes and body) of stream-living brown trout Salmo trutta at temperatures of 3–4 °C in indoor experimental flumes. We hypothesized that an individual's resting metabolic rate (RMR, as measured by resting ventilation rate) would affect winter behavior. Therefore, groups of 4 trout, consisting of individuals with high, low, or mixed (2 individuals each) RMR, were exposed to experimental conditions with or without ice cover. Ice cover reduced stress responses, as evaluated by body coloration. Also, trout in low RMR groups had a paler body color than those in both mixed and high RMR groups. Trout increased their swimming activity under ice cover, with the highest activity found in high RMR groups. Ice cover increased the number of aggressive encounters but did not influence the number of drifting food items taken by each group. In mixed RMR groups, however, single individuals were better able to monopolize food than in the other groups. As the presence of surface ice increases the activity level and reduces stress in stream-living trout, ice cover should influence their energy budgets and production. The results should be viewed in light of ongoing global warming that reduces the duration of ice cover, especially at high latitudes and altitudes.